Mechanistic approach of the electrochemical reduction of CO2 into CO at a gold electrode in molten carbonates by cyclic voltammetry. (2nd November 2016) - Chery, D.; Albin, V.; Meléndez-Ceballos, A.; Lair, V.; Cassir, M.
Abstract: The electrochemical transformation of CO2 into more valuable chemicals such as CO offers great interest in the energetic field. In this paper, the feasibility of this valorisation process is investigated by cyclic voltammetry in different binary molten carbonates: Li2 CO3 Na2 CO3 (52:48 mol. %), Li2 CO3 K2 CO3 (62:38 mol. %) and Na2 CO3 K2 CO3 (56:44 mol. %) and in a ternary eutectic: Li2 CO3 Na2 CO3 K2 CO3 (43.5:31.5:25 mol. %). The eutectic nature, the oxoacidity, temperature and scanning conditions on the reduction and oxidation peaks is thoroughly analysed. The reduction peak related to CO2 reduction into CO is diffusion-controlled and slow quasi-reversible; in specific experimental conditions, it is split into two peaks of similar intensity. Re-oxidation peaks are most probably due to dissolved and adsorbed CO. Based on our experimental investigation under varied conditions such as molten salt composition, oxoacidity, temperature of the system and thermodynamic predictions regarding carbon presence, two mechanistic schemes are proposed, involving gaseous, dissolved and adsorbed species. Highlights: CO2 electrochemical reduction into CO in different molten carbonates eutectics. Effect of the temperature, the oxo-acidity and the nature of the molten carbonates onto CO2 reduction. A diffusion controlled reduction and a quasi-rapid process. Two suggested mechanisms with a 2 electrons process.